Sorafenib and thyroid cancer. Issue 6 (November 2014) - Park, Chandler; Perini, Jessica; Farmer, Roger W; Fancy, Tanya; Monga, Manish; Remick, Scot C
<x xml:space="preserve">Abstract</x> The emergence of serine-threonine small molecule, multi-targeted kinase inhibitors over the past decade is greatly impacting the therapeutic armamentarium for numerous malignancies, especially thyroid carcinoma. Chief among them are a class of agents referred to as vascular endothelial growth factor signal pathway inhibitors. Sorafenib is a lead compound that has been recently approved by the US FDA for radioactive iodine-refractory differentiated thyroid cancer (DTC). Sorafenib clearly is altering the natural history of DTC. In the largest randomized Phase III study ever conducted in DTC, sorafenib significantly improved progression-free survival compared to placebo (10.8 vs 5.8 months) and had an acceptable and manageable safety profile, though commonly attributed side effects of hand-foot skin reaction, diarrhea and hypertension were more frequent than in other settings. This agent represents a new treatment option for patients with progressive radioactive iodine-refractory DTC.